Numerical investigation of shell-and-tube heat exchanger with parabolic segmental baffle cut (2019)
An investigation was carried out on the effect of the use of a parabolic baffle at different baffle cuts on the performance of shell and tube heat exchangers. The numerical study was performed on a personal computer with 12 GB RAM and Intel® Core™ i7 2.50GHz CPU using a CFD software Comsol Multiphysics. The modeled heat exchanger had 37 tubes, shell internal diameter of 200 mm, 6 baffles with baffle spacing of 100 mm. The results from the effect of mass flow rate and baffle cut on heat transfer rate and pressure drop in the shell side of the heat exchanger were compared with the circular segmental baffle cut of 25% and that of the parabolic baffle cut of 25 and 30% of the inner shell diameter. At 25% of the shell diameter baffle cut, the parabolic cut had an improved heat transfer rate compared to that with the circular segmental baffle cut with a drawback of higher pressure drop. As the parabolic baffle cuts increased, there was a decrease in heat transfer rates and pressure drops at the various mass flow rates considered. At 30% of shell diameter cut, the performance of the parabolic segmental baffle cut gave results similar to the circular segmental baffle cut at 25% of the inner shell diameter. The investigation showed that for a parabolic baffle cut, 30% of the shell diameter is recommended for optimum performance.